2019
DOI: 10.3389/fmicb.2019.02559
|View full text |Cite
|
Sign up to set email alerts
|

Indole-3-Acetic Acid in Burkholderia pyrrocinia JK-SH007: Enzymatic Identification of the Indole-3-Acetamide Synthesis Pathway

Abstract: Burkholderia pyrrocinia JK-SH007 is a plant growth-promoting bacteria (PGPB), that can promote the growth of poplar and other trees, and, production of the plant hormone indole-3-acetic acid (IAA) is one of the reasons for this effect. Therefore, the aims of this study were to evaluate the effect of the external environment on the synthesis of IAA by B. pyrrocinia JK-SH007 and to perform a functional analysis of its IAA synthesis pathway. In this study, IAA and its synthetic intermediates indole-3-acetamide (I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
37
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(40 citation statements)
references
References 50 publications
(56 reference statements)
2
37
0
1
Order By: Relevance
“…As reported, the highest IAA yield for B. pyrrocina JK-SH007 was achieved at pH 7.0 and the fastest growth of this strain was observed at pH 4.0 (Liu et al 2019). In our study, the highest yield of IAA was found at pH 5.0 and the optimal growth of the strain was found at pH 5.0-7.0 ( Fig.…”
Section: Molecular Identi Cation Of the Strainsupporting
confidence: 76%
“…As reported, the highest IAA yield for B. pyrrocina JK-SH007 was achieved at pH 7.0 and the fastest growth of this strain was observed at pH 4.0 (Liu et al 2019). In our study, the highest yield of IAA was found at pH 5.0 and the optimal growth of the strain was found at pH 5.0-7.0 ( Fig.…”
Section: Molecular Identi Cation Of the Strainsupporting
confidence: 76%
“…Previous studies on siderophore and pyrroloquinoline quinone biosynthesis have focused on Pseudomonas 42 . Similarly, studies on indoleacetic acid production by PGPR have generally been limited to a few microorganisms such as Azospirillum, Pseudomonas, Rhizobium and Burkholderia 7, [43][44][45][46] . Hence, the identification of Acidocella and Acidobacterium as being potentially involved in these processes, coupled with their hydrocarbon-degrading potentials 18 , significantly expands the range of PGPR applicable for microbially-enhanced phytoremediation of organic pollutants.…”
Section: Discussionmentioning
confidence: 99%
“…Las cepas M15 (B. ubonensis) y M18 (B. cepacia) seleccionadas como BSF produjeron cantidades bajas de compuestos indólicos comparadas con otras cepas de Burkholderia, que han sido reportadas como productoras de este tipo de compuestos empleando la misma metodología para esta determinación. Tal es el caso de Burkholderia heleia PAK1-2 con rendimientos cercanos a 100 µM y capacidad para inhibir patógenos como Burkholderia plantarii (Wang et al, 2016), y Burkholderia pyrrocinia con un máximo de producción de compuestos indólicos de 6,9 mg/L después de 36 horas de cultivo in vitro (Liu et al, 2019). En otros estudios con bacterias aisladas a partir de la rizosfera de mango Mangifera indica L. (Anacardiaceae) reportaron la producción de 2 ± 0,2 mg/L de compuestos indólicos para Burkholderia caribensis (De los Santos-Villalobos et al, 2015).…”
Section: Discussionunclassified